Penggabungan dan Pengembangan Kreativitas Budaya Tradisional dan Budaya Modern untuk Meningkatkan Kesejahteraan Masyarakat menurut Undang Undang Nomor 5 Tahun 2017 tentang Pemajuan Kebudayaan - Tutik Asmorowati; Ainun Nashihah (Yayasan Synto Scientist Center, 2022)
Culture is a way of life that develops and belongs to a group of people which is passed down from generation to generation. While culture is the result of the activities and creation of the culture, according to constitution no 5 of 2017 about the cultural furtherance, “Culture is everything about creativity, taste, intention and result creation of the people” The emergence of a incorporation and development of traditional and modern cultural creativity has led to the emergence of causing factors that lead to legal protections of constitution no 5 of 2017 about the cultural furtherance, so that legal protections can be implemented by the Indonesian government against the society and culture in Indonesia, and that it can improve public welfare. This research is a normative juridical research that is legal research conducted by examining library materials from regulations and literature relating to this issue. The approach taken is the statutory approach.